PENGARUH TERAPI LATIHAN MC KENZIE MENGURANGI KETERBATASAN GERAK THORACAL PADA PEKERJA BATIK DENGAN KELUHAN JOINT BLOCKADE THORACAL - Ade Irma Nahdliyyah; Dani Prastiwi (Pena Jurnal Ilmu Pengetahuan Dan Teknologi, 2015)
Joint blockade thoracal can occur as a result of excessive stretching or contraction and repeated that lasts a long time so that muscles experience spasms that eventually cause  pain resulting in limitation  of  thoracal  movement.  One  effort  that  can  be  done  to  improve  the  in    limitation    of thoracal movement is through Mc. Kenzie Ecercise.This  study  aimed  at  investigating  the  effect  of  Mc.  Kenzie  Ecercise in  increasing  the  functional activity  of  the  batik  craftsmen  with Joint  blockade  thoracal.  This    research  was    a    quasy- experimental    design  with  one  group  pre-test  and  post-test.  The  study  population  was batik craftsmen  in  Sijambe  Village,  Wonokerto,  Wiradesa,  Pekalongan,  amounting  to  80  people. Samples  were  obtained  by  using  purposive sampling  so  that  the  sample  of  20  people. Test used paired sample t-test.The    results    showed    that    the significant  difference  before  and  after  exercise  Mc.  Kenzie  with p=0.000.Keyword : Mc. Kenzie, Excercise, Joint blocade thoracal